Husband Support Through Prenatal Massage for Pregnant Women - Purwandari, Atik; Tuju, Sjenny O; Tombokan, Sandra G.J.; Dompas, Robin (JURNAL PENGABDIAN MASYARAKAT KOMUNITAS KESEHATAN, 2024)
Introduction This community service is a community partnership program (PKM) at the Tompaso Silk Maternity Clinic with the role of the husband of a third trimester pregnant woman. This activity aims to empower the role and support of husbands for pregnant women through Prenatal Massage in the New Normal Era of the Covid 19 Pandemic., objectives to empower the role and support of husbands for pregnant women through Prenatal Massage in the New Normal Era of the Covid 19 Pandemic, methods The method of community service activities is through the Pre/Posttest observation sheet for back pain for pregnant women, providing modules and videos, simulating by the team and the husband practicing on pregnant women for 30 minutes. After that, the Posttest Back Pain Scale for Pregnant women was carried out after the Prenatal Massage was carried out., results From the results of Community Service activities before and after the Prenatal Massage by the husband, there was a decrease in the intensity of back pain before the prenatal massage was carried out with an average value of 45 on a scale of 2 and after a Prenatal Massage the intensity of pain decreased with a value of 30 on a scale of 1, with a difference of 15 before and after after doing Prenatal Massage., and conclusion (that Prenatal Massage by the husband had an effect on reducing pain intensity before the Prenatal Massage was carried out and after the Prenatal Massage was performed. In addition to reducing back pain for pregnant women in the third trimester, it is also useful for providing a sense of comfort during contractions for inpartum mothers in the 1st stage of labor. Prenatal Massage can be done by husband or family at home with Prenatal Massage modules and videos..